Knowledge, Attitudes, Practices, and Prevalence of Dietary Supplement Use Among Medical Students at the National University. - Kumar, Anil; Al Kharusi, Albayan Khalil; Al Nuumani, Eithar Isshaq; Al Khaifi, Alaa Salim; Al-Rubaiai, Alzahraa Rashid; Al-Rawahi, Maryam Abdallah (Journal of Neonatal Surgery, 2025)
Background: The use of dietary supplements (DS) among university students is increasing globally, yet knowledge and safe usage remain limited. Students often rely on unverified information, which may pose health risks. Objectives: To assess the prevalence of DS use among undergraduates at the National University of Science and Technology (NU), and evaluate their knowledge, attitudes, and practices (KAP), including factors influencing consumption. Methods: A descriptive cross-sectional study was conducted from March to April 2025. A self-administered questionnaire was completed by 152 students from three colleges, capturing demographics, DS use, and KAP. Data were analysed using SPSS. Results: DS use was reported by 27.6% of students, with iron (11.2%), multivitamins (9.2%), and vitamins C and D (5.9% each) most common. While 82.2% correctly defined DS, over 60% relied on peers or the internet for information. Although 89.5% supported professional guidance, only 17.1% were tested before use, and just 15.8% adhered to prescriptions. College affiliation was significantly associated with reported side effects (p = 0.012). Conclusion: While students possess basic knowledge of DS, gaps in safe practices and evidence-based guidance remain. Structured education and professional supervision are recommended, particularly for future healthcare professionals.